2013
DOI: 10.1016/j.ejogrb.2013.09.043
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of serum anti-Mullerian hormone levels following hysterectomy and myomectomy for benign gynaecological conditions

Abstract: Serum AMH was significantly lower 2 days and 3 months following hysterectomy compared with the pre-operative level. Following myomectomy, serum AMH was significantly lower than the pre-operative level 2 days following the procedure, but was similar to the pre-operative level 3 months after surgery. Therefore, hysterectomy may have a more lasting adverse effect on ovarian reserve than myomectomy. A long-term study of AMH levels is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 20 publications
(13 reference statements)
4
27
0
1
Order By: Relevance
“…After hysterectomy, AMH level significantly decreased for 3 months. Hysterectomy appeared to affect reserve and function of ovaries significantly compared with myomectomy . In another report regarding the effect of UAE and hysterectomy on ovaries, AMH levels were significantly decreased during the entire follow‐up period in both treatment groups (UAE and hysterectomy) compared with expected AMH levels due to ageing, indicating that both UAE and hysterectomy could affect ovarian reserve .…”
Section: Discussionmentioning
confidence: 93%
“…After hysterectomy, AMH level significantly decreased for 3 months. Hysterectomy appeared to affect reserve and function of ovaries significantly compared with myomectomy . In another report regarding the effect of UAE and hysterectomy on ovaries, AMH levels were significantly decreased during the entire follow‐up period in both treatment groups (UAE and hysterectomy) compared with expected AMH levels due to ageing, indicating that both UAE and hysterectomy could affect ovarian reserve .…”
Section: Discussionmentioning
confidence: 93%
“…Most of the studies surrounding ovarian reserve after a hysterectomy were conducted in non-pregnant, premenopausal patients with reports showing a decline in the serum AMH levels after the hysterectomy. 4,11 On the contrary, other studies reported that ovarian environment was not affected after a hysterectomy and was compensated by the ovarian artery in premenopausal women. 12,13 Limited data is available on ovarian reserve after the management of postpartum hemorrhage including IIAL and/or hysterectomy.…”
Section: Discussionmentioning
confidence: 95%
“…The hysterectomy and its effect on ovarian hormones can be explained by the total occlusion of anastomosing vessels between the ovaries and uterus during the procedure and concomitant impairment in the blood supply of the ovaries. Most of the studies surrounding ovarian reserve after a hysterectomy were conducted in non‐pregnant, premenopausal patients with reports showing a decline in the serum AMH levels after the hysterectomy . On the contrary, other studies reported that ovarian environment was not affected after a hysterectomy and was compensated by the ovarian artery in premenopausal women .…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that hysterectomy damages the function of ovarian secretion to a certain extent, and that the estrogen reduction is more significant. A study [28] also reported that patients with uterine fibroids have a greater effect on ovarian function after hysterectomy, when compared to patients with uterine fibroids removal.…”
Section: Discussionmentioning
confidence: 96%